Peran Klinik Hoaks Kominfo Provinsi Jawa Timur Dalam Meningkatkan Literasi Digital Dan Kepercayaan Publik Pada Informasi Online - Fitria Widiyani Roosinda; Ariyan Alfraita; Prita Sari Dewi Wasista (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2026)
This research explores the role of the Hoax Clinic under the East Java Provincial Office of Communication and Informatics in strengthening digital literacy and fostering public trust in online information, as a response to the rising spread of hoaxes on social media that creates public anxiety and harmful impacts. The study employs a descriptive qualitative approach with data collected through interviews, observations, and documentation. The findings reveal that the Hoax Clinic adopts two strategic approaches: proactive and reactive. The proactive approach is carried out through digital literacy education. The reactive approach involves a structured verification and clarification process for hoax reports submitted by the public, supported with evidence-based explanations and credible references. Overall, the Hoax Clinic demonstrates a strategic role as a fact-checking service by integrating both proactive and reactive efforts in combating misinformation.